Introduction of the magnetic pulse compressor (MPC) - fundamental review and practical application. - Jaegu Choi
Magnetic switch is a kind of saturable inductor, which utilizes nonlinearity of the magnetization curve of ferrogmatic materials. The right understanding of the saturation phenomena, magnetic properties, voltage-time product, and switching characteristics of the magnetic switch is essential in designing the magnetic pulse compressor. In this paper, the historical background of research on the MPC, fundamental physical properties of the magnetic switches, and application fields of the MPC are presented. Further, an in-depth analysis of pulse compression in series and parallel MPCs is incorporated. As practical application examples, a series MPC used for water treatments and parallel MPC used for pulsed electric field (PEF) inactivation of bacteria are cited.
Keywords: Magnetic pulse compressor; Saturable inductor